Religiosity, halal food consumption, and physical well-being: An extension of the TPB - Shahida Suleman; Amena Sibghatullah; Muhammad Azam (Cogent Business & Management, 2021)
This research used the Theory of Planned Behaviour (TPB) theoretical framework to extend and contribute to prior research on halal purchase behaviour. The main purpose of this study is to contribute to the literature by focusing on the relationship between religiosity and physical well-being and identifying the mediating halal-food consumption that affects on physical well-being. We applied non-probability convenience sampling to administer questionnaires among 315 Pakistani Muslim and Non-Muslim respondents currently living in Pakistan, the USA, Canada, Australia, and Germany, during the winter of 2019-2020. The study used a partial-least-squares structural-equation-modeling (PLS-SEM) technique to investigate the data, which provides evidence of reliability and validity. Further, we used the PLS-SEM technique in investigating the relationship among religiosity, halal-food consumption, and physical well-being. The results show that the behavioural intention to buy halal food mediated the relationship between religiosity and physical well-being. Halal-food consumption mediated the relationship between subjective norms and physical well-being. However, it did not mediate the relationship between attitude and physical well-being, perceived behavioural control, and physical well-being. Further, this study also found that behavioural intention to buy halal food has a significant direct positive relationship with religiosity, attitude, subjective norms, and perceived behavioural control. The findings have important implications for food manufacturers and marketers in devising a policy on marketing campaigns to attract very health-conscious customers.
Keywords: 650; religiosity; halal food consumption; theory of planned behaviour; physical wellbeing